1980
DOI: 10.1159/000179108
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Prolactin Cell Hyperplasia

Abstract: In female Long-Evans rats, development of prolactin cell adenomas is preceded by hyperplasia of prolactin cells, suggesting that factors affecting the endocrine function of prolactin cells might have an important role in the genesis of prolactin-producing pituitary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A later study found evidence of prolactin cell hyperplasia (10). A study of male and female Wistar rats revealed a high incidence of spontaneous pituitary tumors and hyperplastic nodules, most of which contained prolactin, and only a few tumors contained GH, TSH, and ACTH (1).…”
Section: Resultsmentioning
confidence: 99%
“…A later study found evidence of prolactin cell hyperplasia (10). A study of male and female Wistar rats revealed a high incidence of spontaneous pituitary tumors and hyperplastic nodules, most of which contained prolactin, and only a few tumors contained GH, TSH, and ACTH (1).…”
Section: Resultsmentioning
confidence: 99%
“…Since an ingrowth of arteries from the dura would bypass the hypothalamus and the classic hypothalamo-hypophyseal circulation, mammotrophs would escape dopamine inhibition with a resultant hypertrophy and hyperplasia. Mammotroph hypertrophy and hyperplasia are known to precede the formation of prolactinomas (Kovacs et al, 1980). The vasculature of the pars distalis of S-D rats (Simonsen Laboratories) did not include arteries or evidence of vascular reorganization comparable to that in F344 rats.…”
Section: Discuss 1 0 Nmentioning
confidence: 99%
“…Based on macroscopic observation, they concluded that arteriogenesis, derived from the dural vessels adjacent to the pars distalis, had occurred in the estrogen-treated Fischer 344 rats, but to a lesser degree in Sprague-Dawley rats. Arteries entering the pars distalis in this manner would contain blood free of hypothalamic inhibitory neurohormones, the absence of which could stimulate the mammotroph hypertrophy and hyperplasia that precede prolactinoma formation (Kovacs et al, 1980). Thus, estrogen may exert its initial influence on prolactinoma formation through an interaction with the vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The escape from hypothalamic inhibitory control leads to lactotroph hyperplasia of the pituitary gland and a high rate of prolactin-producing pituitary adenomas in geriatric rats. 9,13 On light microscopic examination, most prolactin-producing pituitary adenomas of rats contain large spaces filled with RBCs. Large tumors have areas of focal necrosis and macrophage infiltrates.…”
Section: Discussionmentioning
confidence: 99%